Local Food System Development in Hungary - Balázs, Bálint (The International Journal of Sociology of Agriculture and Food, 2012)
This article examines local food system (LFS) development pathways in the context of recent regulatory reforms in Hungary implemented to promote local product sales and short food supply chains (SFSCs). Taking a SFSC approach, two case studies demonstrate how new types of local food systems initiated by non-farmers attempt to shorten the distance between consumers and producers. The findings are based on qualitative key informant interviews and a consumer attitude survey data that seek to identify how LFSs promote or enact sustainable food supply and how consumers perceive the nature of the relationships between consumers and producers. The results from the ‘Gödöll? Local Food Council’ and the ‘Szekszárd local food system’ show various specificities and challenges of new types of emerging urban civic food networks. The article concludes by pointing to critical factors and tools for developing LFSs, as well as reflecting on the role of original research to facilitate change for a more sustainable food system.